Teaching and Learning Modalities in Higher Education During the Pandemic: Responses to Coronavirus Disease 2019 From Spain - Verde, Ana; Valero, Jose Manuel (Frontiers in Psychology, 2021)
The effects of the pandemic have affected and continue to affect education methods every day. Education methods are not immune to the pandemic times we are facing, so teachers must know how to adapt their methods in such a way that teaching, and its quality, is not negatively affected. This paper provides an overview of different types of teaching methodology before, during, and after the COVID-19 pandemic. The following study describes the different types of teaching (presence learning, blended learning, and distance education) used in two Spanish Universities (one private and one public) during the pandemic. A new teaching methodology is proposed. The purpose of this research report is to share what we learned about the response to COVID-19. Results provide a basis for reflection about the pros and cons of teaching and learning modalities in Higher Education. The current situation demands that we continue to rethink what is the best methodology for teaching so that the education of students is not affected in any way. This paper is useful for learning about different teaching methods that exist, and which ones may suit us best depending on the context, situation, and needs of our students.